2022
DOI: 10.1155/2022/4345037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Resolvin D1 and Protectin D1 as Potential Therapeutic Agents for Treating Kidney Stones

Abstract: Intrarenal calcium oxalate (CaOx) crystals induce renal tubular epithelial cell (TEC) inflammatory and oxidative injury. This study is aimed at exploring potential therapeutic lipid components in kidney stones because lipids are involved in the development of several diseases and indicate the risk of kidney stones. Serum specimens were collected from 35 kidney stone patients and 35 normal controls. The lipid components in serum were measured, and differences were analyzed. The documented biological importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Cholesterol accumulation increases plasma membrane stability and protects cells from further toxic damage ( Zager et al, 1999 ). However, if left unchecked, these initially beneficial effects may increase the risk of kidney stones ( Taguchi et al, 2020 ; Wang et al, 2022 ) and progressive renal injury ( Kim et al, 2009 ; Zager et al, 2011 ). In addition, it is reported that renal tubular cell injury is mediated by lipid accumulation associated with changes in gene expression related to cholesterol transport and synthesis ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol accumulation increases plasma membrane stability and protects cells from further toxic damage ( Zager et al, 1999 ). However, if left unchecked, these initially beneficial effects may increase the risk of kidney stones ( Taguchi et al, 2020 ; Wang et al, 2022 ) and progressive renal injury ( Kim et al, 2009 ; Zager et al, 2011 ). In addition, it is reported that renal tubular cell injury is mediated by lipid accumulation associated with changes in gene expression related to cholesterol transport and synthesis ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diseases (reference) Lipoxins ischemic stroke, (115) Alzheimer's disease, (116) multiple sclerosis, (117) gram-negative bacterial pneumonia, (118) pneumococcal pneumonia, (119) allergic rhinitis and asthma, (100) hyperalgesia, (120) periodontitis (121) Resolvin E1 Alzheimer's disease, (116) myocardial infarction, (122) depression, (123) asthma, (124) inflammatory bowel disease, (125) herpes simplex virus-induced ocular inflammation, (126) psoriatic dermatitis, (127) contact hypersensitivity of skin (128) Resolvin D1 depression, (129) emphysema, (130) E. coli-induced pneumonia, (118) pneumococcal pneumonia, (119) non-alcoholic steatohepatitis, (131) kidney stones, (132) diabetic wounds, (133) oral squamous cell carcinoma (134) Maresin Alzheimer's disease, (135) cerebral ischemia/reperfusion injury, (136) asthma, (137) inflammatory bowel disease, (130) diabetic nephropathy, (138) skin inflammation by UVB (139) Protectins epilepsy, (140) influenza infection, (106) kidney stones, (132) wound healing (141) cult. On the other hand, if the mechanism of 5-LOX activation by daidzein is elucidated and compounds that accelerates the production of lipid mediators via induction of LOX activity are developed, they may become new therapeutic agents for influenza.…”
Section: Mediatorsmentioning
confidence: 99%
“…The LC-MS/MS for LMs has been reported previously 27 . Brie y, LMs was analyzed byd by LC-MS/ MS using a Shimadzu LC-20ACXR (Shimadzu, Kyoto, Japan) and Sciex 5500 triple quadruple mass spectrometer (Sciex, MA, USA) with heated electrospray ionization (ESI).…”
Section: Lc-ms/ms For Lipid Mediatorsmentioning
confidence: 99%